Sistem Monitoring Kinerja Panel Surya Secara Real Time Berbasis Web - Sulfikar Sulfikar; A. Irmayani Pawelloi; Andi Muhammad Syafar (Jurnal Mosfet, 2026)
The use of solar energy is increasingly important in addressing climate change. This study designed a real-time web-based solar panel performance monitoring system by monitoring voltage, temperature, and light intensity using Arduino Uno and ESP32 connected to Firebase. Testing was conducted for one day from 08.00-17.00 WITA. In the morning at 09.00, Panel 1 reached a maximum voltage of 22.43 V with a light intensity of 54,612.5 lux and a temperature of 38.4 ℃, while Panel 2 reached 21.67 V with an intensity of 54,612.5 lux and a temperature of 39 ℃, Entering the afternoon at 11.30, Panel 2 recorded the highest voltage of 22.82 V at an intensity of 54,612.5 lux and a temperature of 41 ℃, while Panel 1 showed a voltage of 22.6 V with the same light conditions and a temperature of 39.7 ℃. In the afternoon at 5:00 PM, both panels experienced a significant decrease, where Panel 1 dropped to 8.33 V with an intensity of 13,865 lux and a temperature of 28 ℃, while Panel 2 dropped to 8.45 V with an intensity of 10,918.3 lux and a temperature of 28 ℃. It can be concluded that high light is indeed important in producing electrical energy in solar panels but is not enough if it is not balanced with a relatively low temperature. Optimal conditions are achieved when maximum light is accompanied by a temperature that is not too high, with panel 2 showing slightly more stable performance than panel 1.